How does injury compensation affect health and disability in patients with complaints of whiplash? A qualitative study among rehabilitation experts-professionals. Issue 3 (30th January 2016) - van der Meer, Suzan; Pieterse, Marcel; Reneman, Michiel; Verhoeven, Jan; van der Palen, Job
Abstract: Purpose : To explore rehabilitation professionals' opinions about the influence and the pathways of injury compensation (IC) on health and disability in patients with whiplash associated disorder (WAD). Methods : Semi-structured interviews were performed among a purposeful selected sample of Dutch expert-professionals in the field of rehabilitation of patients with WAD. Inclusion continued until saturation was reached. Inductive and deductive thematic analyses were performed. Results : Ten rehabilitation expert-professionals (five females), working as physician, psychologist or physiotherapist, were interviewed. All expert-professionals acknowledged that IC can influence rehabilitation, health and disability. The expert-professionals provided three causal pathways; a pathway through prolonged distress, a behavioral pathway, and patient characteristics that may either attenuate or worsen their response. They assess the influence of IC mainly with interview techniques. Most professionals discuss the potential influence of IC with their patients, because they want to give clear information to the patient. Some emphasize that their role is neutral in relation with the IC. Others mention that financial consequences can accompany functional improvement. Conclusions : Rehabilitation expert-professionals believe that IC may affect rehabilitation, health and disability in patients with WAD. Three pathways are mentioned by the experts-professionals. Implications for Rehabilitation: According to rehabilitation expert-professionals, an injury compensation (IC) can lead to distress, by creating a (conscious or unconscious) conflict of interests within a patient between striving for compensation on one hand, and recovery on the other hand. Patient characteristics can either attenuate or worsen IC-related distress. Reliable and valid tools need to be developed to assess the influence of IC on health, disability and rehabilitation, and to limit the negative effects. Rehabilitation professionals can discuss the possible unintended effects of IC with their patients to clarify their current situation.